Design and mechanical properties of U-section precast concrete box culverts. (September 2022) - Li, Jilong; Chen, Xin
Graphical abstract: Highlights: Seven simplified two-dimensional models of UPCBCs were proposed. A full-scale static test and a numerical model with seals were studied. Effects of multiple factors on the structural behaviours were investigated. The evaluation index was analyzed, and design suggestions were given. Abstract: To study the joint design of U-section precast concrete box culverts (UPCBCs) and avoid the difficulty in obtaining the stiffness of joints, seven simplified two-dimensional models were proposed based on assumptions of joint constraints. Based on the comparison of internal forces, the cantilever model under axial compression was preliminarily selected to design a single-barrel UPCBC connected by unbonded prestressed bars. A full-scale static test was conducted and numerical model with seals was studied to verify the feasibility of the theoretical models. Furthermore, the effects of multiple factors (theoretical models and prestress) on the structural behaviors (failure modes, bearing capacity and deformation performance) were investigated based on a numerical model with distributed external loads. The evaluation index was analyzed to measure the comprehensive value of culverts, including the consideration of cost, the ability of theoretical models to predict the internal forces, the bearing capacity, and the deformation performance. Based on the results, the conditions of the sliding link model and unbonded prestressed bars (diameter of 12 mm and tensile controlling stress of 0.35 f pu ) were recommended for the design of UPCBCs. Finally, the reliability of the design parameters were proved based on their application to a multi-barrel UPCBC. The results of this study provide a scientific reference for the structural design and applications of UPCBCs.